Abstraction (Chicago Coronet Film & Video, 1988)
Includes archival footage of Kandinsky, Pollock and Barnett Newman in addition to an interview with Frank Stella in his studio. Also shows scenes at the Museum of Modern Art in New York and the Rothko Chapel in Houston.
VHS format.
Written by Henri Zerner.
Keywords: Art, Abstract